Perancangan dan Implementasi Sistem Absensi Berbasis Teknologi Terkini Untuk Meningkatkan Efisiensi Pengelolaan Kehadiran Karyawan dalam Perusahaan - Saied, Muhammad; Syafii, Akhmad (Jurnal Teknik Indonesia, 2023)
This research aims to develop an efficient and reliable attendance system for managing employee attendance within a company. The proposed attendance system is based on state-of-the-art technology that enables more accurate and automated methods. Based on data analysis and literature review, we developed an attendance system that consists of a combination of technologies such as fingerprint recognition, facial recognition, and electronic identity cards. This system is designed to improve the accuracy and efficiency of the employee attendance process. The results of this research indicate that the development of a technology-based attendance system can provide significant benefits for companies. The proposed system enables automatic management of employee attendance, reduces human errors, enhances data security, and reduces the time required in the attendance process. Employees will also benefit from the ease of using this system, such as the ability to quickly and accurately record attendance. In conclusion, this research highlights the importance of developing an efficient and reliable attendance system within a company. By implementing state-of-the-art technology, companies can enhance productivity and efficiency while reducing costs associated with employee attendance management. It is expected that this research can serve as a basis for the development and implementation of improved attendance systems in other companies.